Promising bioactive metabolites of mangrove inhabitant Streptomyces tauricus and prostate cancer PC3 cell inhibition by antimicrobial peptides - Karthik, Yalpi; Kalyani, Manjula Ishwara; Krishnappa, Srinivasa; Ramakrishna, Krishnaveni; Sayed, Samy M.; Aharthy, Ohud Muslat; Alhelaify, Seham Sater; Mushtaq, Muntazir (Frontiers in Microbiology, 2023)
Streptomyces is a group of microbes known for antibiotic production and has contributed to more than 70% of present commercially available antibiotics. These antibiotics are important in the management, protection, and treatment of chronic illnesses. In the present study, the isolated S. tauricus strain from mangrove soil in Mangalore, India (GenBank accession number: MW785875) was subjected for differential cultural characterization, phenotype involving brown pigmentation, filamentous mycelia, and ash-colored spore production was observed using field emission scanning electron microscopy (FESEM) analysis revealing filamentous mycelia possessing a straight spore chain. Spores were visualized as elongated, rod-shaped, smooth surfaces with curved edges. After optimized growth conditions for S. tauricus on starch-casein agar medium, the GC/MS analysis of S. tauricus intracellular extract detected bioactive compounds reported for pharmacological applications. Analyzed using the NIST library, most of the bioactive compounds identified in intracellular extract had molecular weights of less than 1 kDa. On the PC3 cell line, the Sephadex G-10 partially purified eluted peak protein fraction demonstrated significant anticancer activity. The LCMS analysis revealed the presence of Tryprostatin B, Fumonisin B1, Microcystin LR, and Surfactin C with molecular weights below 1 kDa. This study found that small molecular weight microbial compounds are more effective in a variety of biological applications.